The Facies Modeling of Muria Volcano in the Kedungbamban Area Using GIS - Rahmandhala, Ilvan Dino; Supriyadi, Asep Adang; Prihanto, Yosef; Arief, Syachrul; Mulyaningsih, Sri; Wiloso, Danis Agoes (Formosa Journal of Science and Technology, 2024)
Indonesia is an archipelago located in the Pacific Ring of Fire, known for its high volcanic activity. Indonesia is home to 129 active and 500 inactive volcanoes, representing 13% of the world's total. This research is expected to provide an overview of the facies of the Muria volcano and the geological aspects of the study area. To analyze and resolve issues in this study, geological mapping, and data processing are employed to make volcano facies models using GIS.  The volcanic facies in the study area are proximal facies, which can be divided into three zones: proximal facies of Muria basalt, proximal facies of Maar Bambang basanite, and proximal facies of Muria andesite.